1990
DOI: 10.1007/bf00318677
|View full text |Cite
|
Sign up to set email alerts
|

Glucagon-like immunoreactivity in hypothalamic neurons of the rat

Abstract: Antisera specific for three different regions of pancreatic proglucagon were used to examine the distribution of such immunoreactivity in rat hypothalamus. Neurons in the supraoptic and paraventricular nuclei were immunoreactive with an antiserum against glucagon, but not with antisera directed towards the aminoterminal region of proglucagon (glicentin) or the glucagon-like peptide I sequence in the carboxyl-terminal region of proglucagon. These findings confirm a previous report of glucagon-like immunoreactiv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

1992
1992
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 16 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…However, there are data that suggest GLP‐1 may act as a modulator or regulator in the gut–brain axis at different levels. Thus, positive immunoreactivity for GLP‐1 and binding of radiolabelled GLP‐1 have been demonstrated at different levels of the brainstem, such as at the nucleus of the solitary tract (NTS), area postrema, dorsal motor nucleus of the vagus (DMVN), the thalamus or hypothalamus 33–36 . It is conceivable that in the NTS, a region where afferent information from the gut and other organs is integrated, or at the level of DMVN, locally synthesized GLP‐1 induces activation of gastric relaxatory reflex by activation of post‐synaptic neurons involved in vagal nitrergic or adrenergic inhibitory pathways.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, there are data that suggest GLP‐1 may act as a modulator or regulator in the gut–brain axis at different levels. Thus, positive immunoreactivity for GLP‐1 and binding of radiolabelled GLP‐1 have been demonstrated at different levels of the brainstem, such as at the nucleus of the solitary tract (NTS), area postrema, dorsal motor nucleus of the vagus (DMVN), the thalamus or hypothalamus 33–36 . It is conceivable that in the NTS, a region where afferent information from the gut and other organs is integrated, or at the level of DMVN, locally synthesized GLP‐1 induces activation of gastric relaxatory reflex by activation of post‐synaptic neurons involved in vagal nitrergic or adrenergic inhibitory pathways.…”
Section: Discussionmentioning
confidence: 99%
“…Seven (five males and two females) diabetic patients with previously documented cardio-vagal neuropathy were studied. Median age was 65 years (IQR: 56-74) and median body mass index was 26 kg m )2 (IQR: [24][25][26][27][28][29][30][31][32][33][34][35]. Five patients had insulin-dependent diabetes mellitus (IDDM) and two non-insulin-dependent diabetes mellitus (NIDDM); five had diabetic retinopathy; five peripheral somatic neuropathy; four erectile dysfunction; and three renal impairment.…”
Section: Study Conduct and Participantsmentioning
confidence: 99%
“…In the late 80ties, researchers began looking for the new glucagon-like peptides in the brain, inspired by the reports of immunoreactive glucagon in certain neurons of the brain (78), particularly in the nucleus of the solitary tract. These neurons also were immunoreactive for GLP-1 (79). In addition, binding studies suggested the presence of a large number of putative receptors for GLP-1 not only in the beta cells of the pancreatic islets but also in the brain (80).…”
mentioning
confidence: 99%